2013
DOI: 10.1007/s10140-013-1161-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of “bedside ultrasonography” and the “water bath technique” in distal forearm, wrist, and hand bone fractures

Abstract: Bedside ultrasonography (BUS) has been widely used in many emergency evaluations, but the technique was not thoroughly evaluated for use in adult fractures. The water bath technique (WBT) is a modality which overcomes some important limitations of using BUS in extremity fractures. The study aims to evaluate and compare diagnostic values of BUS and WBT. The sensitivity, specificity, positive and negative predictive values (PPV and NPV), positive and negative likelihood ratios (LR+ and LR-), and accuracy of BUS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 23 publications
0
27
0
2
Order By: Relevance
“…Since the eighth edition of the ATLS program (ATLS 2012), FAST has been included as an adjunct to the primary survey in evaluating hypotensive trauma patients. Moreover, use of ultrasound in trauma patients also extends to evaluation of the thorax (extended FAST or E-FAST) (Kirkpatrick et al 2004;Rowan et al 2002;Zhang et al 2006), volume assessment with inferior vena cava (IVC) ultrasound (Ferrada et al 2012;) and fracture detection (Javadzadeh et al 2014;Marshburn et al 2004). The role of contrast-enhanced ultrasound is still investigational, but it is a promising method to assist in detection of abdominal parenchymal organ injuries (Cagini et al 2013;Mihalik et al 2012).…”
Section: Evolution Of Trauma Ultrasoundmentioning
confidence: 97%
“…Since the eighth edition of the ATLS program (ATLS 2012), FAST has been included as an adjunct to the primary survey in evaluating hypotensive trauma patients. Moreover, use of ultrasound in trauma patients also extends to evaluation of the thorax (extended FAST or E-FAST) (Kirkpatrick et al 2004;Rowan et al 2002;Zhang et al 2006), volume assessment with inferior vena cava (IVC) ultrasound (Ferrada et al 2012;) and fracture detection (Javadzadeh et al 2014;Marshburn et al 2004). The role of contrast-enhanced ultrasound is still investigational, but it is a promising method to assist in detection of abdominal parenchymal organ injuries (Cagini et al 2013;Mihalik et al 2012).…”
Section: Evolution Of Trauma Ultrasoundmentioning
confidence: 97%
“…Physicians should be aware that tenderness in the anatomical snuff box (ASB), tenderness over the scaphoid tubercle and pain on longitudinal compression of the thumb have limited added value in a diagnostic process for a scaphoid fracture. The present systematic review identified eight supplementary imaging studies [58,61,65,66,[68][69][70]74], subdivided into MRI [66], CT [58,66,[68][69][70], BS [66] and US [61,65,74]. The overall conclusion is that imaging tests were found to be moderately accurate for a definitive diagnosis.…”
Section: Discussionmentioning
confidence: 91%
“…Radiographs used as an index test for diagnosing scaphoid fractures showed Se, Sp, accuracy, PPV and NPV ranging from 25 to 87%, 50-100%, 48-88%, 14-100% and 49-94%, respectively. For diagnosing scaphoid fractures, Magnetic Resonance Imaging (MRI) as an imaging modality showed Se, Sp, accuracy, PPV and NPV ranging from 67 to 100%, 89-100%, 85-100%, 54-100% and 93-100%, Diagnosing phalangeal and metacarpal fractures in hospital care Table 5 also presents the accuracy of the diagnostic tests for metacarpal and/or phalangeal fractures, as described in six studies [71,[73][74][75][76][77]. Physical examination [77] for diagnosing phalangeal and metacarpal fractures showed Se, Sp, accuracy, PPV and NPV ranging from 26 to 55%, 13-89%, 45-76%, 41-77% and 63-75%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The studies evaluating diagnostic accuracy of sonography for forearm fractures, had been carried out on the pediatric population mostly (Table 5). The gold standard diagnostic tests were x-ray in those studies, therefore false negative results for x-ray imaging had not been reported 6, 7, 8, 9, 10, 11, 12, 13. Our study had some advantages; (1) It has been conducted on the adult patients, therefore our results could be generalized into adult ED patients.…”
Section: Discussionmentioning
confidence: 92%
“…One of the major advantages of POCUS is the opportunity to extensive investigation of the most painful and swelling area. Most of the study assessing sonographic diagnosis of forearm fracture is performed in pediatric patients 6, 7, 8, 9, 10, 11, 12, 13. Distal forearm fracture is one of most managed fracture in emergency department, therefore the new diagnostic algorhythm using US examination for those large ED population may alter emergency medicine practice.…”
Section: Introductionmentioning
confidence: 99%